Chapter Power Struggles in the Management of Wildlife Resources: The Case of Burunge Wildlife Management Area, Tanzania - Mombo, Felister (InTechOpen, 2019)
Through a cross-sectional research design, this study examined power struggles in Burunge Wildlife Management Area (WMA) in Tanzania. Four out of ten villages comprising the WMA were purposively selected, and data were collected via focus group discussions, key informant interviews, questionnaires to household heads, and a literature review. Results showed that the central government, investors and non-government organisations held institutional and strategic powers, while the democratically elected Village Councils held structural powers and lost most of their pre-WMA institutional powers to a legally required new institution, the Authorised Association. Therefore, Village Councils lost influence on strategic, institutional and management decisions pertinent to the WMA and their constituencies' livelihoods. Accordingly, Burunge WMA de-democratised wildlife management by eroding the relevance of Village Councils to their constituencies. The study also found power struggles over revenues, land management and access to resources among the stakeholders, mainly due to a divergence of interests. However, there was no conflict management mechanism in place. Hence, we recommend that the institutional powers to establish, govern and dissolve WMAs should go back to Village Councils. The purpose is to establish economic incentive structures that promote (i) wildlife conservation, (ii) an equitable distribution of associated costs and benefits between Village Councils forming WMAs and (iii) an equitable distribution of costs and benefits between WMAs and higher levels of government as well as international conservation NGOs.